First record and distribution extension of Agalychnis terranova in the Montes de María, Colombia (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
We report a new locality of occurrence of the red-eyed treefrog Agalychnis terranova in the Montes de María, in the department of Sucre, Colombia, which extends its distribution by 187,9 km southwest from its northernmost record in the Sierra Nevada de Santa Marta in the department of Cesar, and 474,6 km to the north from the westernmost locality in the department of Chocó. Finally, we make comments on the biogeography and research perspectives following this new record.